Sebuah TINDAK TUTUR ASSERTIVE DALAM PIDATO RESMI KEJAGUNG BERJUDUL JAKSA AGUNG SEBUT KUALITAS PERTAMAX YANG BEREDAR SUDAH SESUAI SPESIFIKASI PERTAMINA: - - Kharisma Puspita Sari (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
This study aims to analyze the use of assertive speech acts in an official press release by the Chief of the Indonesian Attorney General’s Office, which addressed public concerns over the illegal blending of RON 92 fuel. A descriptive qualitative method was employed, using documentation and indirect observation as data collection techniques. The researcher transcribed into written form and analyzed through pragmatic approach, focusing on identifying assertive speech acts based on Searle’s classifications. Data analysis applied Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings revealed 11 assertive speech acts categorized into four types: stating, reporting, claiming, and concluding. These speech acts functioned to rebuild public trust in Pertamina Patra Niaga and to counter misinformation circulating among the public. This research contributes to the understanding of how institutional communication through assertive speech acts can reinforce public confidence during social controversies.